(untitled) (Research, Society and Development, 2021)
Chronic Kidney Failure is a public health problem because it is a silent multifactorial disease in which diagnosis is usually late and irreversible. The aim of this study was to verify how renal failure determined by creatinine levels above reference values ​​may be related to anemia in these patients. All 4951 exam requests registered in the database of a laboratory in Reserva-PR, from January to December 2020, were selected. After applying the inclusion and exclusion criteria, 105 remained to be analyzed. The inclusion criteria adopted were: patients who underwent blood count and creatinine in the same request, aged between 18 and 60 years, creatinine dosage values ​​above 1.3 mg/dL. Exclusion criteria were: patients under 18 years or over 60 years, with creatinine less than 1.3mg/dL and repeat patients with different requirements. Of the sample of 105 patients, 23.81% (25) were anemic, of which 32% (8) were women and 68% (17) were men. It was found that 75% of anemia in women and 64.70% in men were of the normocytic normochromic type. Chronic kidney disease mainly affects elderly males and anemia is frequent in these patients. Creatinine is an important biomarker and can be used as an adjunct tool in the diagnosis of kidney dysfunction.